домножаем на сопряженное число
(3 - √2)/(√2 - 1) = (3 - √2)/(√2 - 1) * (√2 + 1)/(√2 + 1) = (3√2 + 3 - 2 - √2)/(√2² - 1) = (2√2 + 1)
4√3 / (2√5 - 3√2) = 4√3 / (√20 - √18) = 4√3/(√20 - √18) * (√20 + √18)/(√20 + √18) = 4√3(2√5 + 3√2)/(√20² - √18²) = 4√3(2√5 + 3√2)/2 = 2√3*(2√5 + 3√2) = 4√15 + 6√6
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
домножаем на сопряженное число
(3 - √2)/(√2 - 1) = (3 - √2)/(√2 - 1) * (√2 + 1)/(√2 + 1) = (3√2 + 3 - 2 - √2)/(√2² - 1) = (2√2 + 1)
4√3 / (2√5 - 3√2) = 4√3 / (√20 - √18) = 4√3/(√20 - √18) * (√20 + √18)/(√20 + √18) = 4√3(2√5 + 3√2)/(√20² - √18²) = 4√3(2√5 + 3√2)/2 = 2√3*(2√5 + 3√2) = 4√15 + 6√6